2022
DOI: 10.1186/s12913-022-08914-2
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Black men who have sex with men (MSM) in the South in identifying strategies to increase PrEP uptake

Abstract: Background Promotion, uptake, and adherence of pre-exposure prophylaxis (PrEP) is paramount to ending the HIV epidemic among young Black men who have sex with men in the South. The purpose of this study was to explore strategies needed for and barriers to PrEP uptake needed to achieve HIV prevention goals identified in the U.S. Department of Health & Human Services initiative to reduce new HIV infections in the United States by 90 percent by 2030. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
5
14
0
Order By: Relevance
“…There is great importance in public health practice to identify mental health needs during intake and assessment of clients living with HIV, while linking them to other forms of care in state and federal services, like Ryan White Plan B programs (Kalokhe et al, 2023). These intake processes could be modeled after the psychological and trauma-informed support services offered by CBOs in Memphis to PLWH (Pichon, Teti, & Brown, 2022). In addition, utilizing clinically trained behavioral health specialists who provide care to MSM and other individuals struggling with sexual identity would be a valuable resource for addressing MSM mental health needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is great importance in public health practice to identify mental health needs during intake and assessment of clients living with HIV, while linking them to other forms of care in state and federal services, like Ryan White Plan B programs (Kalokhe et al, 2023). These intake processes could be modeled after the psychological and trauma-informed support services offered by CBOs in Memphis to PLWH (Pichon, Teti, & Brown, 2022). In addition, utilizing clinically trained behavioral health specialists who provide care to MSM and other individuals struggling with sexual identity would be a valuable resource for addressing MSM mental health needs.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing treatment as prevention (TaSP) and U=U campaigns to reduce HIV-and MSM-related stigma in Southern MSM populations vulnerable to or living with HIV could be helpful in other prevention and treatment strategies (National Institute of Allergy and Infectious Diseases, 2019). Extant literature also describes strategies for PrEP navigation and uptake among Memphis-based MSM, with main facilitators through trusted connections, like peers and medical providers who are similar demographics to patients, as well as opportunities for engagement and access (Pichon, Teti, Betts, et al, 2022;Pichon, Teti, McGoy, et al, 2022). Results from the present study can inform these existing and ongoing measures by encouraging the examination of individual and social experiences, including MSMrelated violence, discrimination, and severe PD and how each contributes to PrEP navigation, use, and adherence among Southern MSM populations.…”
Section: Discussionmentioning
confidence: 99%
“…78 Additionally, relatable healthcare providers who use non-stigmatizing language when talking about PrEP have been reported as ways to increase uptake of PrEP among Black MSM. 79 Therefore, efforts should be made to personalize PrEP providers to patients' racial and ethnic preferences. With regard to inclusion of racial minorities in prevention studies, the key PrEP clinical trial, iPrEX, studying daily FTC/TDF, included a large proportion of participants identifying as non-white (9%, 5%, 72%, and 68% selfidentified as Black, Asian, Hispanic, or Latinx and mixed race or other, respectively).…”
Section: Personalizing Prep: Adolescentsmentioning
confidence: 99%
“…In a telephone survey completed in the United States, African Americans, and Latinos reported they perceive racism in the healthcare system and are more satisfied with their care when their own physicians match their own race or ethnicity 78 . Additionally, relatable healthcare providers who use non‐stigmatizing language when talking about PrEP have been reported as ways to increase uptake of PrEP among Black MSM 79 . Therefore, efforts should be made to personalize PrEP providers to patients' racial and ethnic preferences.…”
Section: Pre‐exposure Prophylaxismentioning
confidence: 99%
“…Using qualitative interviews and focus groups, several researchers have found that SMM perceive the focus on SMM to perpetuate stigma [ 19 , 22 24 ]. SMM have highlighted that exclusively focusing on gay men could deter PrEP use among SMM who do not identify as gay or are not open about their sexuality, in addition to excluding other people for whom PrEP is indicated [ 19 , 25 ]. Black SMM have reported that targeted PrEP messaging is stressful and insinuates both that Black SMM are to blame for their HIV risk and that other races do not share that risk [ 19 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%